👤

Przeprowadź redukcję wyrazów podobnych: a) -4a + 5b - 7 - 5a - 4b + 6 = b) 5x + 6y - 7x + 2y - 8x - 8y = c) -12x + 10y - 12x + 12y + 14x - 11y = d) -4x + 4y + 5 - 3y - 2x - 6 + y - 2x + 2=

Odpowiedź :

a) - 9a + b - 1

b) - 10x

c) - 10x + 11y

d) - 8x +2y + 1

a)

-4a + 5b - 7 - 5a - 4b + 6 = (-4 - 5)a + (5 - 4)b + (-7 + 6) = -9a + b - 1

b)

5x + 6y - 7x + 2y - 8x - 8y = (5 - 7 - 8)x + (6 + 2 - 8)y = -10x + 0y = -10x

c)

-12x + 10y - 12x + 12y + 14x - 11y = (-12 - 12 + 14)x + (10 + 12 - 11)y = -10x + 11y

d)

-4x + 4y + 5 - 3y - 2x - 6 + y - 2x + 2 = (-4 - 2 - 2)x + (4 - 3 + 1)y + (5 - 6 + 2) =

                                                                        = -8x + 2y + 1